STRATEGI KOMUNIKASI GEREJA KRISTEN SUMBA UNTUK MENDORONG KETERLIBATAN MASYARAKAT DALAM AKTIVITAS PEMBANGUNAN DESA PAMALAR NUSA TENGGARA TIMUR - Parani, Rizaldi; Naha, Rambu; Purba, Herman (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
The low level of community participation in development activities has driven the Pamalar congregation of the Christian Church of Sumba (GKS) in Central Sumba Regency to play an active role in mobilizing local residents. As a regency with a predominantly Christian population, the church holds a central and strategic position in the community. GKS Pamalar is required to establish strong relationships with the community and adapt to cultural identities to develop approaches based on local wisdom that can encourage community participation in development initiatives. This study aims to analyze the strategies implemented by GKS Pamalar to foster community participation in development activities. To examine this issue, the study employs several key concepts, including strategy, local wisdom, participation, and community development. A qualitative approach with a case study method is used to explore how GKS Pamalar carries out its strategies to build community participation in the development process. The findings indicate that community development programs must be oriented towards the interests and needs of the local population. The success of these programs is also attributed to the active role of the church and its leaders in creating programs related to the main sources of community livelihoods. Furthermore, church leaders often serve as a bridge between the village government and the people of Pamalar. The compatibility of the church leaders’ leadership style in this study is also reflected in their strategies of engagement, recognizing, and directly encouraging participation, which builds a sense of trust — a crucial social capital for driving community development. Keywords: Church Leadership, Community Participation, Community Development, Local Wisdom